Salvage Therapy for Local Progression following Definitive Therapy for Skull Base Chordomas: Is There a Role of Stereotactic Radiosurgery? - Evans, Linton T.; DeMonte, Franco; Grosshans, David R.; Ghia, Amol J.; Habib, Ahmed; Raza, Shaan M. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective The objective of this study was to identify factors associated with improved tumor control at individual sites of recurrence and to define the role of stereotactic radiosurgery (SRS) in the management of local or distant progression following prior radiotherapy.Study Design Clinical data of patients with recurrent skull base chordoma following prior radiotherapy were retrospectively reviewed.Setting and Participants This is a single-center retrospective study including 16 patients from the University of Texas MD Anderson Cancer Center Houston, Texas, United States.Main Outcome Measures Each site of recurrence was considered independently, and the primary outcome was freedom from treatment site progression (FFTSP).Results There were 40 episodes of either local or distant progression treated in 16 patients with skull base chordoma. Tumor recurrence was classified as either local, distant, or both local and distant involving the skull base, spinal column, or leptomeninges. Patients were treated with repeat surgical resection (n = 16), SRS (n = 21), or chemotherapy (n = 25). In multivariate analysis, SRS was the only treatment modality associated with improved FFTSP (p = 0.006). For tumors treated with SRS, there was no evidence of tumor progression or adverse radiation events. Other factors associated with worse FFTSP included the number of progressive episodes (>3), tumor histology, and leptomeningeal disease.Conclusions For local recurrence following prior radiotherapy, SRS was associated with improved FFTSP. SRS may represent an effective palliative treatment offering durable tumor control at the treated site without significant treatment-related morbidity.
Keywords: chordoma; clivus; skull base; radiation; stereotactic radiosurgery